Awareness of the implementation of stable iodine prophylaxis by parental guardians living in the urgent protective action planning zone of an operating nuclear power plant in Japan - Matsunaga, Hitomi; Orita, Makiko; Taira, Yasuyuki; Takamura, Noboru (BMC public health, 2021)
The aim of this study was to clarify the characteristics and awareness of the need for protection against ionizing radiation, such as sheltering, evacuation, and implementing stable iodine prophylaxis, of guardians parenting young children living in an urgent protective action planning zone (UPZ) of an operating nuclear power plant in Japan. Self-administered questionnaires were distributed to approximately 3000 guardians through 26 kindergartens located within a UPZ. Responses were obtained from 1172 who lived in the UPZ and were included in the analysis. Of the 1172 guardians, 460 (39.2%) responded that sheltering is not useful to reduce the dose of radiation exposure. On the other hand, 395 (33.7%) guardians responded that implementing stable iodine (SI) prophylaxis could prevent exposure from all radionuclides, and 876 (74.7%) responded that pregnant women should also implement SI prophylaxis in a nuclear emergency. Furthermore, 83.0% (973) responded that they wanted to receive pre-distribution of stable iodine (PDSI) for their children. On the other hand, 38.9% (456) of guardians had not known about SI before the study, and 71.8% (841) of guardians felt anxious about implementing SI prophylaxis for their children. Most guardians had expectations regarding SI and received PDSI, but they felt anxious about implementing SI prophylaxis for their children. It is essential that guardians living in the UPZ of restarted nuclear power plants be educated, and that risk communication about protection against ionizing radiation, including the side effects of implementing SI prophylaxis and radiation health effects, be conducted.